2010
DOI: 10.1002/app.33087
|View full text |Cite
|
Sign up to set email alerts
|

Structure, properties, and phase transitions of melt‐spun poly(vinylidene fluoride) fibers

Abstract: Three different experimental techniques were used to study structural phase transitions in meltspun poly(vinylidene fluoride) fibers, which were produced with different process parameters and processed in the draw-winding process at different temperatures and draw ratios. The fibers are examined with the help of wide-angle X-ray diffraction at elevated temperatures, differential scanning calorimetry with stochastic temperature modulation, and dynamic mechanical analysis. An oriented mesophase and deformed crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 24 publications
(25 reference statements)
2
32
0
Order By: Relevance
“…The increase in melting point with increased chain length is expected [24] and is partially due to the increased density. It is also consistent with the fact that the α-and β-PVDF crystals with infinite chains gave the highest melting points.…”
Section: α-And β-Pvdf Crystals With Chains Containing 12 and 24 Monommentioning
confidence: 96%
See 1 more Smart Citation
“…The increase in melting point with increased chain length is expected [24] and is partially due to the increased density. It is also consistent with the fact that the α-and β-PVDF crystals with infinite chains gave the highest melting points.…”
Section: α-And β-Pvdf Crystals With Chains Containing 12 and 24 Monommentioning
confidence: 96%
“…Both of these melting points are relevant to the present study, since we simulate crystals made from finite and infinite chains. In addition, recent studies on mechanically drawn PVDF fibres by Steinmann et al [24] showed that and increase in temperature converts the β-PVDF into α-PVDF, which then melts or changes into γ-PVDF. This appears to contradict data that shows that β-PVDF has a higher melting point than α-PVDF [25,26], or that α-and β-PVDF are melting at the same temperature [27].…”
Section: Introductionmentioning
confidence: 99%
“…Possible applications include direction sensitive and spatially resolved strain measurement, which is useful for health monitoring in medical / smart textiles or structural health monitoring in fiber reinforced composites. However, suitable process conditions for fiber spinning, drawing and further processing steps have to be found, whereas phase crystallites have to be formed and not be destroyed along the process chain [39][40][41][42]. Therefore, methods of thermal analysis were developed to identify the presence of the phase, which are validated by additional X-ray diffraction measurements (WAXD) and dynamic mechanical analysis (DMA) [40,42].…”
Section: Poly(vinylidene Fluoride) Fibersmentioning
confidence: 99%
“…However, suitable process conditions for fiber spinning, drawing and further processing steps have to be found, whereas phase crystallites have to be formed and not be destroyed along the process chain [39][40][41][42]. Therefore, methods of thermal analysis were developed to identify the presence of the phase, which are validated by additional X-ray diffraction measurements (WAXD) and dynamic mechanical analysis (DMA) [40,42]. In the following section of this chapter, these methods and their validation will be demonstrated, and they will be applied to gather information about phase transitions during melt spinning, drawing and heat treatment.…”
Section: Poly(vinylidene Fluoride) Fibersmentioning
confidence: 99%
“…It was recently found that the same effect can be achieved with sufficient cold drawing, i.e. drawing in the temperature interval between T g and T m , during the melt spinning process of PVDF textile fibres (Lund and Hagström 2010;Steinmann et al 2011).…”
Section: Introductionmentioning
confidence: 83%